Imperfect oligodendrocytic and neuronal differentiation of glioblastoma cells - Wolańczyk, Magdalena; Hułas-Bigoszewska, Krystyna; Witusik-Perkowska, Monika; Papierz, Wielisław; Jaskólski, Dariusz; Liberski, Paweł P.; Rieske, Piotr (Folia Neuropathologica, 2010)
Previously, we have reported that glioblastoma (GBM) cells can be differentiated into cells showing neuronal, glial and non-neural (mesenchymal) phenotypes. Before the differentiation the GBM cells co-expressed GFAP, CD44, Beta III tubulin, MAP2, Vimentin, Nestin and SOX-2, whereas during the exposure to a neural differentiation medium the differentiation process was arrested at the early stages and the GBM cells presented features of four phenotypes: multi-lineage, non-neural (mesenchymal), intermediate of neuronal cells and glial cells. Currently, we decided to check if changes in expression of: TH (tyrosine hydroxylase, marker of catecholaminergic cells) and GABA (neurotransmitter of GABAergic neurons) and markers of oligodendrocytic cells (O4, CNP) occur during the exposure of GBM cells to the differentiation medium. After exposure to the PDGF alpha and thyroid hormones (oligodendrocytic differentiation medium 10-30 days) features of oligodendrocytic differentiation were presented by 0.2-2.4% of analyzed cells. During the prolonged neural differentiation (GDNF, bFGF 20-30 days) only few cells showed expression of GABA. Moreover, in our cell cultures, there were not cells expressing markers of catecholaminergic neurons – TH. Our work confirmed that the neuronal differentiation of GBM was inhibited at the stage of the neuronal intermediate phenotype. Moreover, we showed that the oligodendrocytic differentiation of GBM cells is very inefficient.